Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/nu12071953
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Insulin Resistance, and Hyperandrogenism Mediate the Link between Poor Diet Quality and Ovarian Dysmorphology in Reproductive-Aged Women

Abstract: The relationship between diet quality and ovarian morphology has biological plausibility yet remains unclear and was therefore evaluated. In a multicenter cross-sectional analysis, four dietary patterns were scored for 111 consecutive reproductive-aged women (18–45 years) using (1) Healthy Eating Index (HEI-2015); (2) alternative HEI-2010; (3) alternate Mediterranean Diet (aMED); (4) and Dietary Approaches to Stop Hypertension (DASH) indices. Ovarian volume (OV) and follicle number per ovary (FNPO) were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 140 publications
0
18
0
5
Order By: Relevance
“…Obesity remains a persistent and growing public health concern, with current rates nearing 40% of reproductive-aged women in the United States [ 1 ]. Obesity impacts a broad array of health risks in women across the lifespan [ 2 ], including adverse reproductive health outcomes such as menstrual cycle irregularity, abnormal uterine bleeding, endometrial hyperplasia, infertility, and pregnancy complications [ 3 , 4 , 5 , 6 , 7 ]. Furthermore, women with obesity are 20% more likely to experience later onset of menopause, which in part may underlie the increased risk of breast, ovarian, and uterine cancer seen in this population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity remains a persistent and growing public health concern, with current rates nearing 40% of reproductive-aged women in the United States [ 1 ]. Obesity impacts a broad array of health risks in women across the lifespan [ 2 ], including adverse reproductive health outcomes such as menstrual cycle irregularity, abnormal uterine bleeding, endometrial hyperplasia, infertility, and pregnancy complications [ 3 , 4 , 5 , 6 , 7 ]. Furthermore, women with obesity are 20% more likely to experience later onset of menopause, which in part may underlie the increased risk of breast, ovarian, and uterine cancer seen in this population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…To that end, an altered ovarian follicular environment has been confirmed in women with obesity and involves disruptions in multiple systems, including steroidogenic action, metabolism, and inflammation, all of which can impact folliculogenesis and ovulatory potential [ 18 ]. The degree to which obesity impacts ovarian reserve is more controversial as available data have largely focused on sub- or infertile populations, wherein studies have not shown consistent associations between serum markers of ovarian reserve and body mass index (BMI) [ 4 , 19 ]. Anti-Mullerian hormone (AMH), a glycoprotein primarily produced by the granulosa cells of primary and early-stage antral follicles, is a marker whose association with obesity is controversial [ 20 , 21 , 22 ]—albeit a single meta-analysis suggests a negative association of AMH with BMI [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Kazemi et al. have evaluated the relationship between four dietary patterns and the overall ovarian function, and found that the latter was affected by diets that influence obesity, metabolic status and hyperandrogenism regulation ( 176 ). The Dietary Approaches to Stop Hypertension (DASH) eating plan has also been previously analyzed by Asemi and colleagues, who highlighted the effect of the DASH diet not only on lipid profiles, but also on oxidative stress markers in PCOS women.…”
Section: Oxidative Stress In Pcos and Cvdmentioning
confidence: 99%
“…Many studies have focused on obesity in women with PCOS by characterizing excessive fat mass (quantity) in a predominantly android fat distribution and impaired fat function (quality). [3][4][5][6][7][8] Accordingly, the adverse effects of altered fat tissue on cardiometabolic 6,[9][10][11][12][13][14] and reproductive [15][16][17][18] complications have been established in PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties also exist in establishing an accurate definition of PCOS status owing to a reliance on a self-reported diagnosis that is unreliable likely leading to misdiagnosis, 35,[57][58][59] unreliable measures of androgen status, 60 and/or ovarian morphology. 18,61,62 Variability in defining control cohorts and heterogeneity in groups' ethnic composition 27 may be contributory.…”
Section: Introductionmentioning
confidence: 99%